Using Google Trends as a Big Data Tool in Digital Journalism - AKTAŞ, SAFA GÖRKEM; ÖZÇAĞLAYAN, MEHMET (My University, 2024)
Big data refers to large volume data sets that emerge with the rapid development of digital technologies today. This data, produced through the internet, social media platforms, mobile devices and other digital sources, accumulates in various formats and at high speed. On the other hand, digital journalism refers to a field in which all processes from news production to distribution are digitalized, which emerged with the adaptation of traditional media to digital platforms. Today, the relationship between big data and digital journalism has become even more evident as news production processes are moved to the digital environment. In this context, the aim of the study is to provide a framework to understand how digital journalism practice changes with the transition from traditional structures to digital technologies and the role of big data in this change. The purpose of the study is to discuss the importance of the use of big data in the field of digital journalism and especially how Google Trends can be evaluated as a big data tool in journalism practice, news reporting and editing process. In line with the purposes of the study, after evaluating the concept of big data, its relationship with search engine-oriented journalism and the aims of Google company, the data presented by Google Trends will be examined within the framework of digital journalism practices. In the context of the information and opinions conveyed, a conclusion emerges that today digital journalism practices cannot be carried out effectively without resorting to big data applications.Keywords:Information technologies, big data, digital journalism, google trends

Büyük veri, günümüzde dijital teknolojilerin hızla gelişmesiyle ortaya çıkan büyük hacimli veri setlerini ifade etmektedir. İnternet, sosyal medya platformları, mobil cihazlar ve diğer dijital kaynaklar aracılığıyla üretilen bu veriler, çeşitli formatlarda ve yüksek hızda birikmektedir. Dijital habercilik ise geleneksel medyanın dijital platformlara uyarlanmasıyla ortaya çıkan, haber üretiminden dağıtımına kadar tüm süreçlerin dijitalleştiği bir alanı ifade etmektedir. Günümüzde haber üretim süreçlerinin dijital ortama taşınmasıyla birlikte büyük veri ile dijital habercilik arasındaki ilişki daha da belirgin hale gelmiştir. Bu bağlamda çalışmanın amacı, geleneksel yapılardan dijital teknolojilere geçişle birlikte dijital habercilik pratiklerinin nasıl değiştiğini ve bu değişimde büyük verinin rolünü anlamak için bir çerçeve sunmaktır. Çalışmanın bir diğer amacı ise dijital habercilik alanında büyük veri kullanımının önemini ve özellikle Google Trends'in haber oluşturma ve düzenleme sürecinde büyük veri aracı olarak nasıl değerlendirilebileceğini tartışmaktır. Çalışmanın amaçları doğrultusunda büyük veri kavramı, arama motoru odaklı habercilik ile ilişkisi ve Google şirketinin amaçları değerlendirildikten sonra Google Trends'in sunduğu veriler dijital habercilik uygulamaları çerçevesinde incelenecektir. Aktarılan bilgi ve görüşler bağlamında, günümüzde dijital habercilik pratiklerinin büyük veri uygulamalarına başvurmadan etkin bir şekilde yürütülemeyeceği sonucu ortaya çıkmaktadır. Anahtar Kelimeler: Bilgi teknolojileri, büyük veri, dijital habercilik, google trends
Dijital Habercilikte Büyük Veri Aracı Olarak Google Trends Kullanımı
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Bilgi teknolojileri; büyük veri; dijital habercilik; google trends; Information technologies; big data; digital journalism